Teachers’ concerns about inclusive education and the links with teachers’ attitudes - Jury, Mickaël; Laurence, Aurélie; Cèbe, Sylvie; Desombre, Caroline (Frontiers in Education, 2023)
The present research investigates teachers’ concerns about inclusive education and said concerns’ specific links with attitudes teachers have regarding this policy. More precisely, while the literature has already identified that teachers share distinct concerns regarding inclusive education (e.g., lack of resources, increased workload, appropriateness, or the difficulties associated with this policy), the first purpose of this exploratory study was to identify whether and how teachers specifically rank these concerns in terms of priority. Additionally, while teachers’ concerns can be negatively associated with attitudes toward inclusive education, the present study also sought to investigate the distinct manner in which teachers’ concerns predict these attitudes. A correlational study involving 508 French teachers was conducted indicating that teachers express the most concern about, by order of descending importance, resources, workload, difficulties, and appropriateness. Moreover, despite the fact that the latter factor was deemed least important, it most consistently predicted the voicing of negative attitudes by teachers toward inclusive education. This interesting paradox, as well as the implications and limitations of the present findings, are discussed.